Hubungan antara Job Crafting dengan Kebermaknaan Kerja pada Guru Sekolah di Banda Aceh - Zahratul Fajri; Irin Riamanda; Mirza; Risana Rachmatan (Jurnal Ilmiah Psikologi MIND SET, 2023)
The role of a teacher encompasses many tasks, which can sometimes diminish the significance of their work and ultimately affect their performance and the quality of education they provide. To enhance the meaningfulness of their work, teachers can engage in job crafting, which involves proactively balancing task demands with available resources. This study aims to explore the correlation between job crafting and work meaningfulness among secondary school teachers in Banda Aceh. The study surveyed 273 secondary school teachers in Banda Aceh who had at least 10 years of work experience, selected through convenience sampling. The study employed quantitative methods with a correlational approach. The findings revealed a positive and significant relationship between job crafting and work meaningfulness. By engaging in job crafting, teachers can customize their work to their preferences and increase their sense of work meaningfulness. This, in turn, can have a positive impact on their performance and the quality of education they provide.